Geology : a complete introduction - Rothery, David A. (London : Teach Yourself, 2015)
We all live on the Earth, but how many of us are aware of the processes that shape - and sometimes shake - its surface? 'Geology' is a comprehensive introduction to the nature and history of the Earth.
Previous edition: 2008.
Includes index.
Keywords: Geology; geology; Popular Science; Geology; Popular Science and Mathematics